Integrated Agribusiness Optimization: Palm-Livestock and Local Wisdom Tolaki Ethnic in North Konawe, Indonesia - Rianse, Ilma Sarimustaqiyma; Baka, Wa Kuasa; Rianse, Usman; Rahadi, Syam; Sarabiah, Sarty (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2023)
The palm oil industry has the potential as a ruminant livestock development area because it holds large feed resources, economic value, and social value. This study explicitly aims to identify the dimensions of the local wisdom of the Tolaki ethnicity regarding buffalo and cattle farming and develop a model for integrating buffalo and cattle farming in oil palm plantations based on the local wisdom of the Tolaki ethnic community in the North Konawe Regency. The research method uses a phenomenological approach and is analyzed descriptively. The research results show the dimensions of the local wisdom of the Tolaki ethnic group in the business of raising buffalo and cattle, including the dimensions of knowledge and skills, the dimensions of social status (Anakia), the economic dimension, and the dimension of obedience to the law. Meanwhile, there are two integration models for the buffalo/cattle livestock business and the oil palm plantation business: the extensive and intensive integration models. The research results, in general, can be concluded that the dimensions of the local wisdom of the Tolaki tribe in integrated cattle/buffalo livestock business in oil palm plantations are divided into 4 parts with extensive and intensive integration models. Keywords: integrated agribusiness, livestock, oil palm, local wisdom